Consumer Perceived Value and Decision Outcome in Multi-Channel Retail : A Systematic Literature Review - Sharma, Dinesh; Panda, Tapan Kumar (Indian Journal of Marketing, 2025)
Purpose : Increasing research on multi-channel identifies various disconnected factors influencing customer decision-making behavior. Collecting and synthesizing this data was imperative to provide practitioners with pertinent insights. This paper examined the current research on multi-channel retailing consumer decision outcomes (CDOs) from the lens of consumer perceived value (CPV). Methodology : This study employed a systematic literature review to delineate the existing knowledge at the junction of CPV and CDO in multi-channel (siloed or integrated) retailing. Findings : A systematic review of 152 peer-reviewed articles published in English-language journals indicated that multi-channel CDOs are predominantly examined as a consequence of the perceived value of multi-channel dimensions rather than linked to retailing marketing and management. This study introduced a conceptual framework for multi-channel CDOs’ antecedents, episodes, and consequences. Practical Implications : The results indicated techniques for utilizing customer decision outcomes to enhance returns for retail marketers and managers. These insights will assist field personnel in attaining consumer decision-making behavior objectives. Originality : This is among the first studies to conduct a systematic review of exhaustive peer-reviewed articles to delineate existing gaps and potential for future research by mapping the intersection of multi-channel customer-perceived value and CDOs. Further, this study provided various findings on retailing studies by segregating findings between articles corresponding to multichannel and omnichannel.